HUBUNGAN PERDAGANGAN INDONESIA-ETHIOPIA DAN IMPLIKASINYA TERHADAP HUBUNGAN DIPLOMATIK KEDUA NEGARA: SUATU TINJAUAN EKONOMI POLITIK INTERNASIONAL - Haniefah Laily Rokhmah Iwf (UIN ALAUDDIN MAKASSAR, 2020)
This study aims to determine the background of Indonesia and Ethiopia conducting trade cooperation which has implications on diplomatic relations between Indonesia and Ethiopia. This study used a qualitative approach, which uses secondary and primary data, where the method of analysis is descriptive analysis. This study uses an analytical framework based on the concept: international trade, national interests and economic diplomacy, and international political economy.The results of this study indicate that the relationship between the political economy of Indonesia and Ethiopia is very closely where this is done through an economic diplomacy. The Economic Diplomacy of Indonesia and Ethiopia is very influential on the development of trade between Indonesia and Ethiopia. In fact, Politics between Indonesia and Ethiopia are only as a political representative, because the driving force of politics between Indonesia and Ethiopia is the economic diplomacy. The motor is the one who makes us move and makes the relationship between Indonesia and Ethiopia are dynamic and increasingly tight.Through economic diplomacy Indonesia and Ethiopia endeavor to establish and improve the bilateral relations that already exist more clearly, planned, systematic and focused to stabilize the diplomatic relations between the two countries and enhancing cooperation in the conducive situation that will produce the pattern and structure of regional security that is based on the economic motives together.